(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2022)
This research article focuses on how it works to teach both speaking domains and fundamental language abilities (how to read, how to listen, and how to speak) (i.e. and vocab, grammatical structure, and pronunciation of words). Since English is the only language in which all topics are taught, it is important to emphasize and utilize texts in English as a foreign learning language as well as the primary considerations for choosing appropriate literary texts. Additionally, there are advantages to teaching language skills through various literary genres (such as poetry, short fiction, drama, and novels), but there are also challenges faced by language teachers when it comes to teaching the English language, including fewer sources of preparation in this area in "TESL "and "TEFL" programs, the nonappearance of specific goals explaining the role of English literature in “ESL” and “EFL”, and English language professors no specific sources or background and training.